Validation of preoperative cardiopulmonary exercise testing-derived variables to predict in-hospital morbidity after major colorectal surgery. Issue 6 (23rd February 2016) - West, M A; Asher, R; Browning, M; Minto, G; Swart, M; Richardson, K; McGarrity, L; Jack, S; Grocott, M P W; Challand, C; Wan Lai, C; Struthers, R; et al.
Abstract: Background: In single-centre studies, postoperative complications are associated with reduced fitness. This study explored the relationship between cardiorespiratory fitness variables derived by cardiopulmonary exercise testing (CPET) and in-hospital morbidity after major elective colorectal surgery. Methods: Patients underwent preoperative CPET with recording of in-hospital morbidity. Receiver operating characteristic (ROC) curves and logistic regression were used to assess the relationship between CPET variables and postoperative morbidity. Results: Seven hundred and three patients from six centres in the UK were available for analysis (428 men, 275 women). ROC curve analysis of oxygen uptake at estimated lactate threshold (V ˙ o 2 at θ ^ L ) and at peak exercise (V ˙ o 2peak ) gave an area under the ROC curve (AUROC) of 0·79 (95 per cent c.i. 0·76 to 0·83; P < 0·001; cut-off 11·1 ml per kg per min) and 0·77 (0·72 to 0·82; P < 0·001; cut-off 18·2 ml per kg per min) respectively, indicating that they can identify patients at risk of postoperative morbidity. In a multivariable logistic regression model, selected CPET variables and body mass index (BMI) were associated significantly with increased odds of in-hospital morbidity (V ˙ o 2 at θ ^ L 11·1 ml per kg per min or less: odds ratio (OR) 7·56, 95 per cent c.i. 4·44 to 12·86, P < 0·001; V ˙ o 2peak 18·2 ml per kg per min or less: OR 2·15, 1·01 to 4·57, P = 0·047; ventilatory equivalents for carbon dioxide at estimated lactate threshold (V ˙ E /V ˙ co 2 at θ ^ L ) more than 30·9: OR 1·38, 1·00 to 1·89, P = 0·047); BMI exceeding 27 kg/m 2 : OR 1·05, 1·03 to 1·08, P < 0·001). A laparoscopic procedure was associated with a decreased odds of complications (OR 0·30, 0·02 to 0·44; P = 0·033). This model was able to discriminate between patients with, and without in-hospital morbidity (AUROC 0·83, 95 per cent c.i. 0·79 to 0·87). No adverse clinical events occurred during CPET across the six centres. Conclusion: These data provide further evidence that variables derived from preoperative CPET can be used to assess risk before elective colorectal surgery. Abstract : Validated risk assessment